Photochemical activity and carbon assimilation by Tamarix ramosissima in coppice dunes in the Gurbantunggut Desert, Northwest China - Li, Guangying; Xu, Yanqin; Zhao, Hui; Zhou, Bingqian; Dong, Zhengwu; Li, Shengyu (Journal of plant ecology, 2025)
This study used a method based on a spatial series in place of a temporal series, selecting Tamarix ramosissima shrubs at different developmental stages of coppice dunes as research subjects to investigate their chlorophyll fluorescence characteristics and non-structural carbohydrates (NSC). The results indicated that: (1) As coppice dunes developed, T. ramosissima showed a significant increase in photosynthetic pigment content alongside a decrease in actual photochemical efficiency (Y(II)). Simultaneously, the reduction state of the plastoquinone (PQ) pool intensified, the apparent electron transport rate (ETR) increased, and the quantum yield of regulated energy dissipation significantly increased. These adaptations enabled T. ramosissima to dissipate excess light energy by enhancing its non-photochemical energy dissipation mechanisms. (2) Photosynthetically active radiation (PAR) and T. ramosissima leaf temperature (TL) gradually increased during coppice dune development, whereas soil water content decreased, leading to increased stress on T. ramosissima and a subsequent decline in NSC content. This increased stress placed T. ramosissima at risk of ‘carbon starvation’, resulting in a gradual reduction in photosynthesis, biomass accumulation, and ultimately, mortality. (3) Correlations among various indicators of T. ramosissima were significant, with the highest degree of association and marked enhancement of synergistic effects in the growth and stable stages of coppice dunes. Comprehensive analysis revealed that high soil moisture content can alleviate water stress, improve light energy use efficiency and enhance the photosynthetic carbon assimilation process in T. ramosissima during coppice dune development.